The Influence of Study Habits, Nutritional Status and Economic Level on Physical Fitness - Nelsa, Remon; Damrah, Damrah; Putra, Aldo Naza; Arsil, Arsil; Andika, Heru (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2024)
The aim of this research is to see the direct or indirect influence of study habits, nutritional status and economic level on the physical fitness of students at SMA N 7 Kerinci. This type of quantitative research uses a comparative causal approach, the population in this study was 101 class X students of SMA N 7 Krinci and the sample used was 30 people with sampling using random sampling. The research instruments used were questionnaire sheets for study habits and economic level variables, the Indonesian Student Fitness Test (TKSI) for physical fitness variables and body mass index (BMI) measurements for nutritional status variables. The data obtained will be analyzed using (Part Analysis). The results of the research and analysis show: (1) There is a direct influence of study habits on physical fitness, with a Py1 of 0.316 or 9.98%. (2) There is a direct influence of nutritional status on physical fitness, with a Py2 of 0.306 or 9.93%. (3) There is a direct influence of economic level on physical fitness, with a py3 of 0.461 or 21.25%. (4) there is no influence of study habits through economic level on fitness, with a p-value of 0.289 > 0.05. (5) There is no influence of nutritional status through economic level on physical fitness, with a p-value of 0.235 > 0.05. (6) There is an influence of study habits, nutritional status and economic level together on physical fitness with an Rsquare value of 0.399 or 39.9%.